Dislocation dynamics simulations in the presence of interacting cracks - GÜLLÜOĞLU, ARİF NİHAT (ASME-AMER SOC MECHANICAL ENG, 1999)
For an understanding failure behavior of crystalline solids, considerable interest is given to investigating interaction effects between the main crack and microcracks in the presence of mobile dislocations. Accurate analysis of these types of interaction problems may lead to accurate models for failure prevention and the history of plastic zone development. High stress concentration areas such as crack tips are the places where dislocations are subjected to higher forces. Therefore, a computer simulation technique based on dislocation dynamics has been developed to investigate the movement of dislocations in the presence of multiple cracks. Dislocation structures, dislocation distribution and strain rate results are presented as functions of applied stresses for different microcrack positions and orientations. Simulation results give a reasonable description of dislocation pattern development during deformation around the cracks and explain the shape and development of the plastic zone.
Keywords: MAIN CRACK; MICROCRACKS